2019
DOI: 10.3390/app9050950
|View full text |Cite
|
Sign up to set email alerts
|

Special Issue on ‘Large Grid-Connected Wind Turbines’

Abstract: The renewable energy penetration rate to the power grid is rapidly increasing these days [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…Currently, the world's largest wind turbine has a diameter of 220 m for 12-13 MW of power production [30]. The same blade diameter is used in the proposed design here.…”
Section: Turbine and Propellersmentioning
confidence: 99%
“…Currently, the world's largest wind turbine has a diameter of 220 m for 12-13 MW of power production [30]. The same blade diameter is used in the proposed design here.…”
Section: Turbine and Propellersmentioning
confidence: 99%
“…The windmill and wind pump were built in Iran in the 9th century [35], and were initially used for grinding grain and pumping water. Renewable energy penetration in the electricity grid is increasingly growing at the moment [36], and recent research from 2019 [37] has shown that the overall renewable energy potential, excluding hydropower, is 1.081 GW. Wind energy is the most appealing choice in the renewable energy industry.…”
Section: Wind and Wind Farms In Iranmentioning
confidence: 99%
“…Among the renewable‐based energy systems, wind energy is one of the fastest growing renewable sources. The capacity of modern wind turbine has increased from 10 to 30 kW in 1979 11 to more than 9.5 MW in recent years 12,13 . The continuous growth of wind energy has accelerated the interest in the development and manufacturing of large machines leading to an intense competition between the giants of wind turbine manufacturers.…”
Section: Introductionmentioning
confidence: 99%
“…The capacity of modern wind turbine has increased from 10 to 30 kW in 1979 11 to more than 9.5 MW in recent years. 12,13 The continuous growth of wind energy has accelerated the interest in the development and manufacturing of large machines leading to an intense competition between the giants of wind turbine manufacturers. Indeed, in March 2018, GE debuted its own 12 MW Haliade-X turbine [13][14][15] and the machine has racked up numerous orders, including for the world's biggest offshore wind farm that will be built off the coast of England.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation